PEMBUATAN FLIPBOOK KEANEKARAGAMAN HAYATI SEBAGAI MEDIA PEMBELAJARAN KELAS X SMA - Sari, Ermeisa Dini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed at determining the production of flipbook and the feasibility as a biodiversity learning media for X grade senior high school. This research consisted of two phases. The first phased is production of flipbook media. The second phased is feasibility of flipbook media. This research form was quantitative descriptive. The sampling techniques was purposive. The flipbook media validation had been done by two Biology Education Lecturers of FKIP UNTAN and three X grade senior high school biology teachers in three schools in in Sambas Regency. Based on the flipbook media validation, got a value Content Validity Index (CVI) as big as 0,99, which indicated that flipbook media valid or feasible as a media for learning biodiversity material.Keywords : Biodiversity, Flipbook, Production